Effects of Process Parameters on Electrical Discharge Machining Performance Measures on D3 Steel - Amit Hazari; Amir Sohel; Arijit Halder; Sabuj Sarkar; Rajib Samanta; Bibek Kumar Das (International Journal of Engineering and Management Research, 2021)
One of the most significant factors to consider in the majority of manufacturing processes, particularly those involving Electrical Discharge Machining, is the proper selection of manufacturing conditions (EDM). It can machine geometrically complex or hard material components that are precise and difficult to machine, such as heat treated tool brass, copper, steels, composites, super alloys, ceramics, carbides, heat resistant steels, and so on. It is widely used in the die and mould making industries, aerospace, aeronautics, and nuclear industries. According to the literature review, some study has been done to determine the ideal levels of machining parameters that provide the greatest machining quality in the machining of difficult-to-machine materials such as hot die steel H-11 and D3 STEEL. H-11 hot die steel is widely utilised in hot-work forging, extrusion, punching tools, mandrels, mechanical press forging dies, plastic mould and die-casting dies, aviation landing gears, helicopter rotor blades and shafts, and other applications. A comparative examination of electro discharge machining (EDM) of D3 STEEL alloy employing brass electrodes was conducted as part of this project. Material removal rate (MRR) and overcut were used to evaluate the process' performance. During the testing, the pulse on time, pulse off time, and peak current were varied, and a brass electrode with a tubular cross section was used to cut through holes in a D3steel alloy workpiece. The machined surfaces were subjected to metallographic examination. To limit the overall number of tests, a well-designed experimental system was adopted. The whale's optimization algorithm was used for some of the experiment. The goal of this study was to look at the impact of various EDM process parameters on machining quality and to come up with the best set of process parameters to improve the quality of machined parts. The EDM process parameters' working ranges and levels are determined using a one-factor-at-a-time approach. The Taguchi technique was used to examine the effects of EDM process parameters and, as a result, forecast sets of ideal parameters for the best quality attributes. The empirical models for response characteristics were developed using response surface methodology (RSM) in conjunction with second order central composite rotatable design. Desirability functions were utilised to optimise multiple performance measurements at the same time. Confirmation experiments on the whale's optimization algorithm are also carried out to verify the results.